PENGARUH KONTEN PEMASARAN DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN PRODUK SOMETHINC PADA APLIKASI TIKTOK - Sari, Galuh Permata; Marlena, Novi (Program Studi Pendidikan Tata Niaga Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2024)
Marketing content is created so that the audience is interested in the products the company offers, marketing content can also be used to build the company's brand image. Brand image can reflect a brand through consumer perception. This research aims to determine the impact of marketing content and brand image on purchasing decisions. This research is a quantitative type of research obtained from primary data through distributing questionnaires. The population in this study was 100 respondents. The sampling method uses random sampling. Data analysis uses multiple linear regression and is calculated using IBM statistics 23. The results of this research are that marketing content and brand image influence purchasing decisions. In improving purchasing decisions, companies can build good marketing content and brand image, both of these things can increase consumer trust. to make a purchase.